Oral quinine pharmacokinetics and dietary salt intake. - Newton, P; Simpson, A; Wanwimolruk, S; Maliakal, P; Villegas, L; Kuypers, D; White, N (2001)
OBJECTIVES: The objective was to determine whether or not dietary salt intake affects the relative bioavailability of oral quinine. Salt intake has been shown to alter quinidine bioavailability. METHODS: The pharmacokinetic properties of oral quinine sulphate (600 mg salt) were investigated in seven healthy Caucasian volunteers, in a randomised, crossover study, on low- and high-salt diets. Plasma quinine concentrations were measured by high-performance liquid chromatography (HPLC) and the 24-h urinary sodium excretion was assayed. RESULTS: Although the 24-h urine sodium excretion was significantly higher when the volunteers were on a high-salt diet, there were no significant differences in quinine AUC0-infinity, tmax, and Cmax after the two diets. The median (range) quinine elimination half-life was significantly shorter after a high-salt diet [8.5 (4.3-10.2) h] than after a low-salt diet [10.0 (7.6-14.8) h] (P = 0.04). CONCLUSION: Dietary salt does not affect the relative oral bioavailability of quinine sulphate.